Fatal Epstein-Barr Virus Reactivation in an Acquired Aplastic Anemia Patient Treated with Rabbit Antithymocyte Globulin and Cyclosporine A - Tohru Takahashi; Yumiko Maruyama; Mayuko Saitoh; Hideto Itoh; Mitsuru Yoshimoto; Masayuki Tsujisaki (Case Reports in Hematology)
Epstein-Barr virus (EBV) associated lymphoproliferative disorder (LPD) after immunosuppressive therapy for aplastic anemia (AA) is extremely rare in a nontransplant setting and has not been well described. This report describes a severe AA patient in whom fatal EBV-LPD developed after being treated with rabbit antithymocyte globulins (ATG) and cyclosporine A (CsA). An 81-year-old man was diagnosed as having severe AA. He was started on CsA followed by administration of ATG for five consecutive days. One month after the start of ATG, persistent fever which was not responsive to antibiotics or antifungal agents developed and atypical lymphocytes emerged in peripheral blood. Repeated blood cultures were negative. An extremely high level of EBV virus in his peripheral blood plasma was detected by means of a quantitative real-time PCR assay. Even after the cessation of CsA, the fever persisted and the peripheral atypical lymphocytes proliferated rapidly. The patient suffered from respiratory failure, liver dysfunction, and metabolic acidosis. Rituximab was administered without success and he died.